Tumour necrosis factor α converting enzyme (TACE) activity in the colonic mucosa of patients with inflammatory bowel disease. Issue 1 (1st July 2002) - Brynskov, J; Foegh, P; Pedersen, G; Ellervik, C; Kirkegaard, T; Bingham, A; Saermark, T
Abstract : Background: Anti-tumour necrosis factor α (TNF-α) antibodies are effective in Crohn's disease and perhaps ulcerative colitis but antigenicity and the high cost have raised interest in other strategies to block TNF-α. These include the TNF-α converting enzyme (TACE) which releases soluble TNF-α from transmembrane pro-TNF-α. Aim: To investigate whether TACE activity is present in human colonic mucosa. Materials and methods: Detergent extracts of cell membranes from colonic biopsies were obtained from 12 controls and 28 patients with inflammatory bowel disease. Enzyme activity was measured by hydrolysis assays using pro-TNF-α or oligopeptide substrates spanning the known pro-TNF-α cleavage site at Ala(76)-Val(77). Cleavage products were identified by western blotting, high pressure liquid chromatography, or mass spectrometry. TACE protein was localised by immunohistochemistry and identified by western blotting of detergent extracts from purified lamina propria mononuclear cells (LPMNC) or epithelial cells. Results: Detergent extracts released TNF-α from pro-TNF-α and cleaved a model oligopeptide as predicted. Substrate hydrolysis was sensitive to known TACE/matrix metalloproteinase (MMP) inhibitors, but not trocade which has low activity against TACE. The median TACE level was increased in active ulcerative colitis (147 arbitrary units (AU)/mg; p<0.01) but not in Crohn's disease (81 AU/mg) compared with controls (79 AU/mg). Both the full length proform and the active form of TACE protein were expressed in LPMNC cells and epithelial cells. Conclusions: Functional TACE activity is ubiquitously expressed in the human colon and increased in ulcerative colitis, raising interest in MMP inhibitors targeting TACE.